2018
DOI: 10.1016/j.mce.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Tissue control of androgen action: The ups and downs of androgen receptor expression

Abstract: Please cite this article as: Hunter, I., Hay, C.W., Esswein, B., Watt, K., McEwan, I.J., Tissue control of androgen action: The ups and downs of androgen receptor expression, Molecular and Cellular Endocrinology (2017), doi: 10.1016/j.mce.2017 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 109 publications
2
21
0
Order By: Relevance
“…The importance of the AR signaling pathway in the male reproductive system has been studied in depth. The promoter for the AR gene lacks a typical TATA box and, in agreement with many TATA-less genes, transcription is driven primarily by binding of the zinc finger transcription factor Specificity Protein 1 (Sp1) to GC box regulatory elements [50]. In human prostate cancer LNCaP cells, inhibition of Sp1 activity results in a strong decrease in the AR protein level [51], showcasing Sp1 relevance in the regulation of AR transcription.…”
Section: Sertoli Cell Maturation During Postnatal Developmentmentioning
confidence: 99%
“…The importance of the AR signaling pathway in the male reproductive system has been studied in depth. The promoter for the AR gene lacks a typical TATA box and, in agreement with many TATA-less genes, transcription is driven primarily by binding of the zinc finger transcription factor Specificity Protein 1 (Sp1) to GC box regulatory elements [50]. In human prostate cancer LNCaP cells, inhibition of Sp1 activity results in a strong decrease in the AR protein level [51], showcasing Sp1 relevance in the regulation of AR transcription.…”
Section: Sertoli Cell Maturation During Postnatal Developmentmentioning
confidence: 99%
“…It is well known that androgens can increase muscle mass and strength, 7,8 but they are not routinely used to treat these disorders because of their unfavourable side effects in cardiovascular, liver, and reproductive tissues. The androgen receptor (AR) is a nuclear receptor that plays a critical role in the function of several organs including the prostate, testis, ovary, skeletal muscle, and bone 9,10 . AR is activated by binding to ligands such as androgens, after which it translocates into the nucleus, where it binds to androgen response elements within the promoters or enhancers of androgen‐responsive genes such as E‐cadherin 11 and fibroblast growth factor 8 12 .…”
Section: Introductionmentioning
confidence: 99%
“…However, multiple mechanistic studies have found that the observed antiproliferative effects of the PPARγ agonists occur via PPARγ‐independent pathways . Perhaps the most important of these pathways in PCa is the enhancement of proteasomal degradation of Sp1, a transcriptional factor essential for the expression of multiple genes including the AR . Knockdown of Sp1 by siRNA can reduce the mRNA levels of AR and attenuate AR‐dependent gene transcription .…”
Section: Marine Sponge–derived Compoundsmentioning
confidence: 99%
“…Knockdown of Sp1 by siRNA can reduce the mRNA levels of AR and attenuate AR‐dependent gene transcription . Furthermore, Sp1 undergoes nontranscriptional inhibition by activated AR …”
Section: Marine Sponge–derived Compoundsmentioning
confidence: 99%